The Amagugu intervention to increase disclosure of maternal HIV to HIV-uninfected primary-school aged children in Southern Africa: A randomised controlled trial - Rochat, T; Stein, A; Cortina-Borja, M; Tanser, F; Bland, R (Elsevier, 2017)
Background As HIV preventive efforts improve, an increasing population of preadolescent HIV-exposed but uninfected children face significant developmental and health challenges, including disclosure of parental HIV. The aim of this research is to test the efficacy of the Amagugu intervention to increase maternal HIV-disclosure to HIV-uninfected children aged 6-10 years, leading to improvements in health care engagement and custody planning. Methods Individually randomised efficacy trial in rural KwaZulu-Natal, South Africa; follow-up to nine months. We used computer-generated simple random sampling with blinded assessment. The Amagugu intervention included six home-based counselling sessions; the enhanced standard of care included one clinic-based counselling session. The primary outcome was maternal HIV-disclosure (full, partial, none) measured at 9-months using an intention to treat analysis Findings We consecutively approached 634 women at four primary health care clinics (July 2013-December 2014). 464 mothers were randomised (Amagugu intervention n=235; enhanced standard of care n=229); 428 (92%) completed the 9-month assessment (September 2015). The Amagugu intervention led to an increase in any disclosure (204/235 vs. 128/229 aOR 9.88 [5.55-17.57] p<0.001) and full disclosure using the words ‘HIV’ (150/235 vs. 98/229 aOR 4.13 [2.80- 6.11] p<0.001). Time to full disclosure was shorter in the intervention group (median 2.83 vs. ESC median 9.10 months [log-rank test p<0001]). More mothers in the intervention group took their child to a clinic visit (aOR 31.49 [17.51-56.61] p<0.001), discussed a care plan (aOR 3.56 [1.64-7.69] p=0.001), and appointed a guardian (aOR 22.22 [1.25-3.94] p=0.001). There were no treatment related deaths; but 21 unrelated adverse events (intervention group=17; enhanced standard of care group=6). Conclusions and Relevance This trial of a psychological intervention, the first from a low-resource setting, demonstrated positive outcomes. The counsellor-driven intervention changed maternal behaviours achieving high rates of mother-led HIV disclosure, enhanced health education and custody planning. Longer term follow-up and effectiveness research is required.